2005
DOI: 10.1007/s00216-005-0105-7
|View full text |Cite
|
Sign up to set email alerts
|

New type of dry substances content meter using microwaves for application in biogas plants

Abstract: Dry substances (DS) are an important index for monitoring and controlling anaerobic co-digestion in biogas plants. We have developed and tested an online meter that measures suspended solids by means of the reflection coefficient of an exiting microwave signal, which is dependent on the dielectric properties of the suspensions. Intelligent models based on partial least squares regression (PLSR) and artificial neural network (ANN) for calibration allow exact and reproducible measurements under different circums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Multivariant data analysis was shown to be a suitable approach for detecting organic dry mass in biogas plants [48]. The data have been reduced to a combined parameter derived from a narrow spectrum between 2.2 and 2.6 GHz which is in first approximation the reflection coefficient at 2.45 GHz.…”
Section: Dry Matter In Slurries and Mashesmentioning
confidence: 99%
“…Multivariant data analysis was shown to be a suitable approach for detecting organic dry mass in biogas plants [48]. The data have been reduced to a combined parameter derived from a narrow spectrum between 2.2 and 2.6 GHz which is in first approximation the reflection coefficient at 2.45 GHz.…”
Section: Dry Matter In Slurries and Mashesmentioning
confidence: 99%
“…The use of microwave technology yields a non contact method for monitoring the substrate within tanks of biotechnological plants [24]. Using an economic, narrow bandwidth method with sophisticated post processing (principal component analysis), it was shown that the determination of total organic mass is accurate enough for controlling a biogas plant.…”
Section: Measurement Of Content Of Organic Dry Substancesmentioning
confidence: 99%
“…Even more critical, there are few methods available for online monitoring of total solids. However, Luck et al [19] and Nacke, et al [20], reported on-line monitoring of solids in biogas plant using microwaves and NIR spectroscopy, respectively. On the other hand, one of the limitations in non-invasive NIR methodology is the need to construct optical aperture in the process line.…”
Section: Dry Matter (Ts) Monitoringmentioning
confidence: 99%
“…The optical aperture is liable to fouling by microbial growth and may reduce effective process monitoring over a long period of time [4,18]. Also, in both studies [19,20] optimal validation with independent test set samples were lacking which is a cause of critical concern for future prediction purpose [21]. 6…”
Section: Dry Matter (Ts) Monitoringmentioning
confidence: 99%